The measurement of the GDP and the well-being of the people - Szretykó, György; Mészáros, Attila (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2025)
The air pollution activity, cigarette advertisements, deforestation and the sacrificing of natural wonders forgrowth is included in the GDP as a value. While our children’s health, the quality of our education or the joy that is causedby playing with their parents is not. Moreover, GDP is not increased by the beauty of our poetry and the power of marriages. To cut the whole thing short, GDP considers everything but the important things in life.’Robert Kennedy, 1968.The subjects of this essay are definition, limits and critique of GDP. At the same time it presents the reasons and goals of creating of Stiglitz Committee, sketches 12 suggestions developed by the Committee. Among the alternative indexes elaborated for measurement of GDP, this essay gives detailed analyses of Better Life Index (BLI) and Human Development Index (HDI). Regarding welfare and sustainable development realised at the same time, the essay analyses the practice of Bhutan Kingdom and initiative of Germany. It concludes that the suggestions of the Stiglitz Committee are very correct and well-established, but every document is worth as much as it realised in practice.